Dampak Perbedaan Pola Asuh Orang Tua Terhadap Pertumbuhan dan Perkembangan anak di Desa Bangun Rejo KecamatanTanjung MorawaTahun 2024 - Indra Agussamad; Lisdayanti Simanjuntak; Ingka Kristina; Zulkarnein Batubara; Pangaribuan Pangaribuan; Lilis Hartati Berutu; Yessy Winata Hutagalung (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Receiving care from parents is a child's right. However, the absence of parents in a child's life means that a child does not receive care from his parents. The absence of parents is a condition where the whereabouts of the child's parents are unknown or other conditions which prevent the child from getting his right to be cared for. However, this can be overcome by providing alternative care. Alternative care is care that is carried out based on a substitute family or Child Welfare Institution. Service activity method with structured lectures and guidance. The results were that participants were very enthusiastic in participating in service activities by STIKes Mitra Husada Medan lecturers regarding parenting styles for parents in educating their children at home. So that insight and knowledge increase. The following are community service activities, especially parents, starting from providing material by the Lecturer Team headed by Indra Agussamad, S.Kep, M.Kes and members Lisdayanti Simanjuntak, Ingka Kristina and 2 students.